Stereo vision calibration procedure for 3D surface measurements - Vilaça, João L. (2006)
In reverse engineering, rapid prototyping or quality control with complex 3D object surfaces, there is often the need to scan a complete 3D model using laser digitizers. Those systems usually use one camera and one laser,- using triangulation techniques; complex 3D objects can cause information gaps in the model obtained. To overcome this problem, another camera can be used. Traditional calibration procedures for those systems normally result in a full 3D camera calibration, involving individual implicit camera parameters, a rigid motion equation relating the explicit cameras parameters of each camera and the intersection with the laser line. This paper presents a new stereo vision laser strip calibration procedure for 3D surface measurements. In this calibration procedure the laser plane is the one that matters, only one set of laser-coplanar calibration points for camera calibration is needed, and a dead zone scan area is considered, since the digitalization arm is mounted in a 3 degree freedom machine PC-based Motion Control with multiple scan paths.